Regional expression of neuropeptides in the retina of the terrestrial slug Limax valentianus (Gastropoda, Stylommatophora, Limacidae). Issue 10 (20th January 2022) - Matsuo, Ryota; Matsuo, Yuko
Abstract: Gastropods use lens‐bearing eyes to detect ambient light. The retina contains photoreceptors that directly project to the brain. Here, we identified the neurotransmitters that the retinal cells use for projection to the brain in the terrestrial slug Limax . We identified 12 genes encoding neuropeptides as well as a novel vesicular glutamate transporter, a marker of glutamatergic neuron, expressed in the retinal cells. Spatial expression profiles of the neuropeptide genes were determined by in situ hybridization. WWamide/MIP1/Pedal peptide2 were coexpressed in the neurons of the accessory retina. In the main retina, prohormone‐4 was expressed in the ventrolateral region. Clionin was expressed in the ventromedial region. Pedal peptide was expressed in the anterior region of the main retina and in the accessory retina. Enterin was expressed in many neurons, including the accessory retina, but not in the dorsal region. FxRIamide1 and 2 were coexpressed in the posterior region. Prohormone‐4 variant was uniformly expressed in many neurons but scarcely in the accessory retina. MIP2 was widely expressed throughout the dorsoventral axis in the posteriolateral region of the main retina. Myo1 was expressed in many neurons of the main retina but predominantly in the dorsal region. These expression patterns were confirmed by immunohistochemistry with specific antibodies against the neuropeptides. Projections of these peptidergic retinal neurons were confirmed by immunostaining of the optic nerve. Our present study revealed regional differentiation of the retina with respect to the neurotransmitters that the retinal cells use. Abstract : Generally, retinal photoreceptors in the retina are thought to be uniform with respect to the neurotransmitters they contain. In the study of Matsuo and Matsuo, at least 12 different neuropeptide genes are found to be expressed in a region‐specific manner in the lens‐bearing eye of the terrestrial slug Limax .